Comparison of king vision video laryngoscope versus mccoy laryngoscope for endotracheal intubation in patients with immobilized cervical spine - Jitendra Kumar Yadav; Raj Kumar Harshwal; Savita Meena; Neelu Sharma; Sukirti Sharma; Jain Prashant Abhay (Journal of Applied Pharmaceutical Research, 2023)
Background: Objective of this study was to compare King vision video laryngoscope versus McCoy laryngoscope for endotracheal intubation in patients with simulated immobilized cervical spine in terms of mean intubation time and number of attempts and successful intubation. Methodology: This was a prospective randomized study of 70 patients of ASA Grade I or II and aged 18- 60yrs, who underwent elective surgery under general anaesthesia. Intubation was done with either King Vision video laryngoscope (channelled blade) [Group A] or McCoy laryngoscope [Group B] after immobilizing the cervical spine using a cervical collar. We compared the mean intubation time, success rate and intubation difficulty using the Intubation Difficulty Score (IDS), glottic visualization using POGO score, hemodynamic parameters and complication if any. Results: Both the groups were comparable regarding the demographic variables such as age, sex, weight and ASA class. The mean intubation time of patients in Group A was significantly less (16.57 Â± 4.11 seconds) than Group B (20.14 Â± 5.72 seconds) (P= 0.004). IDS and POGO scoring were found significantly better in group A as compared to group B. But intubation success rate was 100% in both groups. Hemodynamic parameters and complications were also comparable. Conclusion: King Vision video laryngoscope is found superior to the McCoy laryngoscope if cervical immobilization is anticipated in terms of ease of intubation and glottic visualization.